Identification of Landslide-Prone Areas in Bukik Lantak Timpeh Subdistrict Dharmasraya Regency Using the HVSR Method - Andesta, Cindy (Department of Physics, Universitas Negeri Padang, 2025)
Landslides are one of the natural disasters caused by the movement of soil or rock masses downhill. Landslides are caused by disturbances in the stability of the soil or rock that make up the slope. One of the areas frequently affected by landslide is Timpeh Subdistrict. Therefore, microtremor data collection was conducted at Bukik Lantak, Timpeh Subdistrict, Dharmasraya Regency to determine the predominant frequencies and amplification factors in the region, utilizing the Horizontal to Spectral Ratio (HVSR) method. Furthermore, the dominant frequency and amplification values were processed to determine the seismic vulnerability index and shear wave velocity were used to identify areas prone to landslides. Based on the analysis of microtremor data, the dominant frequency values ranged from 0.1 to 9.55 Hz, amplification factor values ranging from 1.11 to 4.12, seismic vulnerability index values between 0.3052 and 15.376, and shear wave velocity values ranging from 120 m/s to 1800 m/s. Areas with high landslide potential are those with a combination of low dominant frequency values, low shear wave velocity, high amplification factor values, and high seismic vulnerability indices. Areas meeting these criteria are located at research points TP1, TP3, TP5, TP7, TP15, and TP16.